Técnicas exegéticas y su incidencia en la comprensión lectora de los estudiantes de cuarto año de educación básica de la Unidad Educativa “Fausto Misael Olaya Gaybor”, de la Parroquia Pimocha, cantón Babahoyo, Provincia de Los Ríos - Ruiz Bastidas, Susy Elvira (2019)
The purpose of this research is to determine if exegetical technique improves reading comprehension in the fourth year students of basic education of the Educational Unit "Fausto Misael Olaya Gaybor". This technique has the objective that the student captures and understands what the author wants to communicate and seeks the meaning implicit in the text, as well as their circumstances. Each student can rely on the topic that most interests them to inquire about it. Again, new technologies provide us with a great advantage in the use of this technique, since they allow us access to an unlimited amount of information. And to achieve the objectives of the investigation, an objective test was developed, which was applied at the end of the process. Exegetic technique improves meaningful learning in student reading comprehension It is proposed to train and update teachers, in the understanding and application of exegetic technique. To contribute to education since this technique is to make the student come into contact with the works of an author or with significant sources, so that he reads them and interprets them properly for the study of a subject